Cybernetics & Postcolonial Landscape: Exploring a New way to Understand the Power and International Governance in Contemporary Era - Huang, Yuwei; Wu, Yun (Journal of Theory and Practice of Management Science, 2023)
In posthumanism, the cybernetics serves as the striking feature as it acts as the fundamental technology to support the operation of machine. The postcolonial landscape as the modern technology-based world, somewhat, features the key elements cybernetics such as circularity, complexity, and self-regulation etc. The technology in postcolonial time brings the voice of grassroots (including the colonized nations) into the social system of international governance which constitutes an unprecedented power in postcolonial landscape. The colonial period has been brought into an end; however, comprehending the postcolonial landscape proves to be considerably more challenging. International governance is no longer solely a tool for military conquest, but rather an intricate and multifaceted network characterized by circularity, complexity, and self-regulation. In line with these attributes, cybernetics illuminates our understanding of power and international governance in the contemporary era while offering a fresh perspective that rejects linearity and unidirectional patterns. The role of technology at this key period of time has transcended its mere function of convenience and societal facilitation, now reshaping the dynamics of human interaction as well as the power dynamics between colonizing and colonized states. This paper aims to delve into the contemporary relationship among various post-colonial powers and their governance strategies through a cybernetic lens.